Emily Gold’s Posttraumatic Stress Disorder in Jodi Picoult’s The Pact - Amanda Sugiarto; Priska Febrinia (Institute of Research and Community Outreach - Petra Christian University, 2013)
This article aims to discuss Emily Gold’s Posttraumatic Stress Disorder, how it affects her way of viewing expectations coming from people around her, and the effects of the failure in fulfilling the expectations. It is found that Emily’s conditions as a PTSD sufferer makes her to perceive the expectations as rules to be obeyed and also as her redemption. When she fails to fulfill the expectations, she uses self-injury as her way of shouting out the pain and to punish herself. Later, when self-injury fails to accommodate her pain and anxiety, she decides to commit suicide to end her sufferings. In conclusion, Emily’s traumatic experience, and later her mental condition as a PTSD sufferer give a tremendous impact towards her way of perceiving expectations coming from people around her.